An Inexpensive Device for Multiple Depth Sampling of Groundwater Quality in Cohesionless Aquifers - Wendy D. Graham (EDIS)
This document is CIR943, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date May 1991. Reviewed July 2002.